2015
DOI: 10.4314/jasem.v19i2.4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Mercury on Seed Germination and Seedling Growth of Mungbean (<i>Vigna radiata</i> (L.) Wilczek)

Abstract: Among the toxic elements release in the environment, mercury is considered highly toxic to the growth of plants. The present studies report the effects of different concentrations (1, 3, 5 and 7 mM) of mercury on seed germination and seedling growth performance of mungbea (Vigna radiata) as compared to control. Mercury treatment in the form of mercuric chloride at 1 mM did not show significant reduction in seed germination of V. radiata as compared to control. Increase in concentration of mercury to 3 mM produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“…When the interaction values were evaluated overall, Cd, Hg and Ni heavy metals had more negative effects on RRL than others. Similar to our findings, the negative effects of heavy metals on root growth have been reported by other researchers (Mishra and Choudhuri, 1998;Peralta et al, 2001;Verma and Dubey, 2003;Dabhi et al, 2005;Şahin and Kıran, 2005;Gyawali and Lekhak, 2006;Ayhan et al, 2007;He et al, 2014;Muhammad et al, 2015;Gedik et al, 2015;Akar and Atış, 2019). Means of RSL were given in Table 8.…”
Section: Resultssupporting
confidence: 91%
“…When the interaction values were evaluated overall, Cd, Hg and Ni heavy metals had more negative effects on RRL than others. Similar to our findings, the negative effects of heavy metals on root growth have been reported by other researchers (Mishra and Choudhuri, 1998;Peralta et al, 2001;Verma and Dubey, 2003;Dabhi et al, 2005;Şahin and Kıran, 2005;Gyawali and Lekhak, 2006;Ayhan et al, 2007;He et al, 2014;Muhammad et al, 2015;Gedik et al, 2015;Akar and Atış, 2019). Means of RSL were given in Table 8.…”
Section: Resultssupporting
confidence: 91%
“…As we found that the growth of B. napus was adversely impacted by higher amounts of Hg (8 ppm) relative to the corresponding controls. Previously, the tolerance of seedling growth was well explained in cotton by Iqbal et al [ 69 ] and barley by Qadir et al [ 70 ]. Heavy metal stress affects several plant species [ 71 ]; some plant species can bear heavy metal stress.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, Baruah, et al [51] reported reduced germination rates in pea and tomato seeds, while Abusriwil, et al [52] observed this effect in Madia sativa. Additional studies by Muhammad et al [53] and Ahemad [54] have also documented the inhibitory effects of high mercury and cadmium concentrations on seed germination.…”
Section: Effect Of Heavy Metal Tolerant Psb On Tomato Seed Germinationmentioning
confidence: 94%